2020
DOI: 10.1002/prp2.577
|View full text |Cite
|
Sign up to set email alerts
|

Trends in opioid prescribing in Estonia (2011‐2017)

Abstract: Our objective was to examine the trends and variation in opioid prescribing in Estonia from 2011 to 2017. This retrospective cross‐sectional study is based on a nationwide prescription medicines database. We stratified the analysis by treatment indication (cancer vs noncancer pain). Between 2011 and 2017, annual opioid prescribing rates increased by 67% (from 82.9 to 138.6 prescriptions per 1000 population). The annual number of prescriptions per patient did not change substantially (from 2.94 in 2011 to 2.87 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
2
1
Order By: Relevance
“…In terms of consumption, our results report a DID (DDD per 1000 inhabitants per day) between 7.1 and 6.7 for all OA, for tramadol between 5.7 and 5.6 and for strong opioids between 1.5 and 1.2 DID, which is 10x lower compared to Ireland (Norris et al., 2021) and 5x lower compared to Spain (Hurtado et al., 2020). However, our results report a higher consumption compared to Estonia, and seem to be close to the recently published data from Hungary (Engi et al., 2022; Uusküla et al., 2020) A similar regional division was observed by Ju et al., where the overall consumption of OA (ambulatory and hospital use) in Slovenia is half of the consumption in Western and Central Europe, but substantially higher than the consumption in Eastern European countries (Ju et al., 2022).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In terms of consumption, our results report a DID (DDD per 1000 inhabitants per day) between 7.1 and 6.7 for all OA, for tramadol between 5.7 and 5.6 and for strong opioids between 1.5 and 1.2 DID, which is 10x lower compared to Ireland (Norris et al., 2021) and 5x lower compared to Spain (Hurtado et al., 2020). However, our results report a higher consumption compared to Estonia, and seem to be close to the recently published data from Hungary (Engi et al., 2022; Uusküla et al., 2020) A similar regional division was observed by Ju et al., where the overall consumption of OA (ambulatory and hospital use) in Slovenia is half of the consumption in Western and Central Europe, but substantially higher than the consumption in Eastern European countries (Ju et al., 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports showed differences in prevalence and consumption of AO among European regions and countries. The reported annual prevalence is lower than the reported prevalence in Ireland (Norris et al, 2021), and Finland (Muller et al, 2019), but higher than the reported prevalence in Estonia (Uusküla et al, 2020).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Opioids are widely used in the treatment of acute pain, cancer pain, and chronic non-cancer pain [ 4 , 6 , 9 ]. The use of these analgesics has been increasing [ 37 ], especially in patients without cancer compared with those with neoplasias (75% vs. 29%) [ 38 ]. However, there is a growing controversy regarding their use to treat non-oncological pain because this recommendation is based on limited evidence and because their long-term effectiveness is poor [ 37 ].…”
Section: Discussionmentioning
confidence: 99%